Psychophysiological Effects of Biographical Interventions in People With Unresponsive Wakefulness Syndrome and Minimally Conscious State - Grimm, Teresa; Groß, Martin; Nater, Urs M.; Summ, Oliver; Kreutz, Gunter (Frontiers in Neurology, 2022)
Background: Various music interventions can evoke favorable behavioral responses or physiological reactions in people with disorders of consciousness (DOC) such as coma, unresponsive wakefulness syndrome (UWS) and minimally conscious state (MCS). However, it appears that no study thus far has investigated the effects of music on the endocrine system of people with DOC. Objective: This explorative study aimed to investigate the effects of biographical music and biographical language on the physiological and endocrine system of people with UWS and MCS. Method: A cohort of 20 people with DOC (10 females, 10 males; age range 19–77) received 20 minutes biographical music and biographical language. Before and afterwards, they were exposed to silence. Physiological and hormonal measurements were conducted before, during and after the interventions. Results: Paired t-tests showed a significant decrease of salivary cortisol in the condition with biographical language interventions. Conclusion: Biographical interventions can modulate reactions in the endocrine system in people with DOC. Further studies are needed to establish whether and how individuals living with DOC show psychoneuroendocrine responses to music and other arts-based interventions.